A systematic review of noninvasive and invasive sialorrhoea management. Issue 23 (8th August 2019) - Varley, Li Ping; Denieffe, Suzanne; O'Gorman, Claire; Murphy, Annette; Gooney, Martina
Abstract: Aims and objectives: To review published literature pertaining to the management of sialorrhoea while also highlighting the significance of the multidisciplinary approach. Background: Sialorrhoea is a common and troublesome problem among certain neurological patients. It is distressing for patients and caregivers, and can be challenging for healthcare professionals. Various sialorrhoea management approaches have been documented. However, there is no clear consensus on best management practices. Therefore, it is necessary to systematically review and synthesise various approaches so as to provide an understanding of the efficacy of management approaches. Design: Systematic literature review using PRISMA checklist (see Appendix S1). Method: Five databases (ScienceDirect, Wiley Online Library, CINAHL, Cochrane Library and PubMed) were searched (years 2001–2018) following inclusion criteria. Out of 1, 294 identified records, 29 studies met the inclusion criteria. Results: Various management approaches identified, ranging from noninvasive, such as speech therapy aiming to enhance swallowing behaviour, to invasive treatment including anticholinergic medication, botulinum toxin injection and surgical techniques. However, in the majority of cases, there is no scientific evidence‐based management protocol leading to favourable results, and the evidence base for intervention effectiveness remains weak. Conclusions: The multifactor nature of sialorrhoea and its associated complications presents challenges for the medical care team. None of the management strategies stand alone as the best modality; therefore, it is proposed that management strategies follow a multidisciplinary approach to meet the diverse needs of patients. Relevance to clinical practice: A comprehensive understanding of different sialorrhoea management approaches will enable healthcare professionals to identify the signs and symptoms regarding sialorrhoea, and to assist in effective management implementation. This will help to improve the management of sialorrhoea, hence, to improve quality of life of patients and provide formative scope to the development of an integrated care pathway.